The Transport-Production Coordination Problem - Jaroslav Janacek (Communications - Scientific letters of the University of Zilina, 2007)
Vehicle route planning process, which follows a transportation problem solution, often provides a system of cyclic routes of vehicles. This system should cover transportation demands of individual network nodes within a middle term period. Due to non-uniform demand distribution over the period, a new problem emerges in particular parts of the period. This problem consists in balancing the sub-period demands and frequencies, with which the individual routes are performed. This new problem denoted as the transport-production coordination problem is studied in this contribution.We described the problem by mathematical programming tools and proposed a decomposition method to enable the problem decomposition to irreducible sub-problems. The individual types of the problem were studied and particular solving algorithms were designed. To complete our approach to this NP-hard problem, we developed an exchange heuristic and explored its properties. The associated computational study was performed with several series of the irreducible sub-problems, which were solved by the exchange heuristic and, simultaneously, they were solved to optimality by the universal optimization environment Mosel. The results were used for evaluation of the heuristic quality and time consumption.